2017
DOI: 10.1785/0220160210
|View full text |Cite
|
Sign up to set email alerts
|

On‐Demand Custom Broadband Synthetic Seismograms

Abstract: We present a new web service, Syngine (http://ds.iris.edu/ds/products/syngine/), running at the IRIS DMC, that offers on-demand and custom tailored seismograms over a broad period range from 1 to 100 seconds, served over HTTP. The free service produces full seismic waveforms including effects like attenuation and anisotropy that are calculated in commonly used spherically symmetric Earth models (PREM, ak135-f, iasp91). Users can freely adjust sources and receivers, retrieve seismograms from finite sources, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…We request the vertical components of the synthetic global broadband seismogram for the iasp91_2s model from the IRIS Syngine Data Service (Krischer et al, 2017) powered by the spectral-element program AxiSEM (Nissen-Meyer et al, 2014) and the Python packages Obspy and Instaseis (Van Driel et al, 2015). A mask is applied to the full waveforms ( Fig.…”
mentioning
confidence: 99%
“…We request the vertical components of the synthetic global broadband seismogram for the iasp91_2s model from the IRIS Syngine Data Service (Krischer et al, 2017) powered by the spectral-element program AxiSEM (Nissen-Meyer et al, 2014) and the Python packages Obspy and Instaseis (Van Driel et al, 2015). A mask is applied to the full waveforms ( Fig.…”
mentioning
confidence: 99%
“…speeding up data retrieval by parallelization and bulk requests 7. demonstrate obspyDMT's plotting capabilities as we go 8. apply instrument corrections to waveform data 9. retrieve synthetic seismograms from Syngine (Synthetics Engine) web service (Krischer et al, 2017), to match observed seismograms.…”
Section: Guided Tour Of Use Casesmentioning
confidence: 99%
“…waveforms from a new IRIS web service: Syngine (Krischer et al, 2017) and (2) providing required metadata for calculating synthetic waveforms using external tools.…”
Section: Requesting Synthetic Seismogramsmentioning
confidence: 99%
“…ObsPy (Beyreuther et al, 2010;Megies et al, 2011;Krischer et al, 2015) is currently running and tested on Linux (32 and 64 bit), Windows (32 and 64 bit) and Mac OS X. Please refer to the ObsPy web page for complete notes regarding ObsPy installation on different platforms.…”
Section: Appendix A: Directory Structurementioning
confidence: 99%
“…obspyDMT is part of the ObsPy ecosystem (Beyreuther et al, 2010;Megies et al, 2011;Krischer et al, 2015), an open-source community project that develops Python software for seismological observatories under the GNU Lesser General Public License, hosted by the Ludwig-Maximilians-Universität Munich. ObspyDMT uses many of ObsPy's utility functions, as well as functions from Python's numpy, scipy and matplotlib libraries (Hunter, 2007), combining them into a more specialized piece of software.…”
Section: Introductionmentioning
confidence: 99%